Convocation, Northeast Missouri State Teachers College, Kirksville, Mo., August 07, 1942 - Northeast Missouri State Teachers College (Kirksville, Mo.) (1942)
This convocation program shows the class roll on August 07, 1942 at the Northeast Missouri State Teachers College in Kirksville, MO.